Good roads and good streets - Hallsted, Alanson L (My University, 1903)
Introduction: A road has been defined as a public thoroughfare, or that on which one rides or travels; a road or avenue cut in a wood or through grounds to be used as a place of travel. The word is generally applied to highways, and as a generic term it includes highways, street and land. When the first settlers came to this country they found nothing but dense wilderness. The streams of water were their only roads, and because of this fact they were compelled to locate along the streams in order to communicate with each other. They soon became dissatisfied with this only means of travel because of the long distance they were sometimes compelled to go owing to the crookedness of the stream, so they began to penetrate the wilderness and use the old Indian trails for roads. These were soon widened into bridle paths and later were made into wagon roads, but no efforts were yet made to smooth the rough places or bridge the streams. As the country became more densely settled the demand became greater for direct and better roads to the landings, which became the distributing centers. In response to this demand a public road system was inaugurated. Improvement was then begun by laying out wider and straighter roads and improving them in the worst places. In a good many parts of the country no further efforts toward improvement have been made and today we find these roads just the same as they were then. We are glad, however, to note that in most parts of the country development has continued although in some places at a very slow rate, yet they have made considerable improvement so that their roads are much better than the first.
Citation: Hallsted, Alanson L. Good roads and good streets. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Agricuilture; Sugar Beets; Theses